Eine neue Chironomidenart aus dem Bodensee. Chironomidenstudien I. (Diptera: Chironomidae). - Reiss, Friedrich (Contributions to Entomology = Beiträge zur Entomologie, 1964)
There are described adult male and pupa of a new species of Chironomidae, Cryptotendipes Pflugfelden n. sp. from the Lake of Constance and given notes on the phenology of the adults and the ecology of the larvae. By means of single rearing of the early stages their affiliation was examined and secured. There is added a key for the identification of male adults and pupae of the known European species of the genus Cryptotendipes Lenz. Nomenclatural Acts pflugfelderi Reiss, 1964 (Cryptotendipes), spec. n.